Anti-N-methyl-D-aspartate-receptor encephalitis: diagnosis, optimal management, and challenges - Mann AP; Grebenciucova E; Lukas RV (Dove Medical Press, 2014)
Andrea P Mann,1 Elena Grebenciucova,2 Rimas V Lukas21Department of Psychiatry and Behavioral Neuroscience, 2Department of Neurology, University of Chicago, Chicago, IL, USAObjective: Anti-N-methyl-D-aspartate-receptor (NMDA-R) encephalitis is a new autoimmune disorder, often paraneoplastic in nature, presenting with complex neuropsychiatric symptoms. Diagnosed serologically, this disorder is often responsive to immunosuppressant treatment. The objective of this review is to educate clinicians on the challenges of diagnosis and management of this disorder.Materials and methods: A review of the relevant literature on clinical presentation, pathophysiology, and recommended management was conducted using a PubMed search. Examination of the results identified articles published between 2007 and 2014.Results: The literature highlights the importance of recognizing early common signs and symptoms, which include hallucinations, seizures, altered mental status, and movement disorders, often in the absence of fever. Although the presence of blood and/or cerebrospinal fluid autoantibodies confirms diagnosis, approximately 15% of patients have only positive cerebrospinal fluid titers. Antibody detection should prompt a search for an underlying teratoma or other underlying neoplasm and the initiation of first-line immunosuppressant therapy: intravenous methylprednisolone, intravenous immunoglobulin, or plasmapheresis, or a combination thereof. Second-line treatment with rituximab or cyclophosphamide should be implemented if no improvement is noted after 10 days. Complications can include behavioral problems (eg, aggression and insomnia), hypoventilation, catatonia, and autonomic instability. Those patients who can be managed outside an intensive care unit and whose tumors are identified and removed typically have better rates of remission and functional outcomes.Conclusion: There is an increasing need for clinicians of different specialties, including psychiatrists, neurologists, oncologists, neuro-oncologists, immunologists, and intensivists to become familiar with this disorder and its potential complications. Remission can be optimized with prompt detection and aggressive, collaborative treatment within a multidisciplinary team.Keywords: anti-NMDA receptor, encephalitis, management, treatment, complications, paraneoplastic